Galaxies in the universe:an introduction - Sparke, Linda S.; Gallagher lll, John S (Cambridge, Cambridge University Press, 2007)
This extensively illustrated book presents the astrophysics of galaxies since their beginnings in the early Universe. It has been thoroughly revised to take into account the most recent observational data, and recent discoveries such as dark energy. There are new sections on galaxy clusters, gamma ray bursts and supermassive black holes. The authors explore the basic properties of stars and the Milky Way before working out towards nearby galaxies and the distant Universe. They discuss the structures of galaxies and how galaxies have developed, and relate this to the evolution of the Universe. The book also examines ways of observing galaxies across the whole electromagnetic spectrum, and explores dark matter and its gravitational pull on matter and light. This book is self-contained and includes several homework problems with hints. It is ideal for advanced undergraduate students in astronomy and astrophysics.
Appendix A-C, 407-420p.; Index 421-431p.
Keywords: Glaxies in the universe; Physics